Old wine region, new concept and sustainable development: winery entrepreneurs' perceived benefits from wine tourism on Spain's Canary Islands - Alonso, A.; Liu, Yi (Routledge, 2012)
Much of wine tourism research underlines the many benefits of this concept for wineries, the wine sector and rural areas. Few studies, however, have taken a longitudinal approach to investigate (1) the extent to which wineries become involved in wine tourism, (2) whether they actually benefit from it over time and (3) what impediments, if any, prevent them from maximising the opportunities that wine tourism may provide. This study builds upon existing research to investigate the perspective of small winery entrepreneurs on Spain’s Canary Islands. After years of planning and expectations concerning the potential of wine tourism, overall respondents indicate very little progress in wine tourism development. The majority of those involved (59%) are only marginally or not benefiting from it at all. Winery entrepreneurs believe that wine tourism’s potential is yet to be exploited, but little government support, lack of organisation within the wine sector and limited resources continue to impede its adoption. Although opportunities exist to market wines among some segments of the nine million tourists who visit the Canaries annually, research, partnership creation and marketing needs to be done at stakeholder level (government, wine sector and tourism agencies) to create a sustainable business concept.